Liberalization of the Swiss Letter Market and the Viability of Universal Service Obligations - Christian Jaag (Swiss Journal of Economics and Statistics, 2007)
We discuss the ongoing liberalization process in the market for addressed letter mail in Switzerland. The paper assesses the impact of the liberalization on the financial viability of various universal service obligations with and without access to the incumbent's downstream delivery network for customers and competitors. We propose a calibrated model of the Swiss letter market offering theoretical insights into the mechanics ofmarket opening alongwith quantitative conclusions bearing direct policy relevance. It turns out that full market opening would require a sharply reduced uso with respect to the frequency and the coverage of delivery or a sharp price increase.
Keywords: H44; L52; 330; Liberalization; Mail; Universal Service Obligation